Identification of miRNA-3652 Signature as a Promising Diagnostic Biomarker in FFPE Tissues of Breast Cancer Patients - Lina Abdulfatah Abdulrazaq; Jamal Hidayat , Hazha (Zanco Journal of Pure and Applied Sciences, 2025)
Researchers have recently begun to investigate microRNAs (miRNAs) as a potential new class of biomarkers. In this study, we examine whether miR-3652 may be regarded as a powerful biomarker for predicting the prognosis of breast cancer (BC). In this study, the expression level of miR-3652 was detected in 30 FFPE tissue pairs of tumoral samples and their adjacent non-tumoral tissues using qRT-PCR. The clinicopathological characteristics of patients relative to miR-3652 expression level, along with fold change analysis employing the 2-ΔΔCT method, were also investigated. All statistical analyses were conducted using GraphPad Prism version 8.4.3 (686). We found that the miR-3652 level in BC FFPE tissues is notably increased compared to matched non-cancerous specimens. Also, we analyzed the association between the expression level of miR-3652 and the clinicopathological parameters of BC patients. The overexpression of miR-3652 exhibited no significant association with age, tumor stage, ER status, PR status, TNM stage, or calcification. All HER2-negative status patients suggested a potential trend (P = 0.017), indicating that low miR-3652 expression was more common in HER2-negative status subjects. Moreover, the p-value, AUC, Std. Error, sensitivity, and specificity are (p < 0.018, 0.6772, 0.06905, 0.53, and 0.80, respectively), which signifies a moderate capacity of the test to differentiate between patients with tumors and controls. The results of fold change analysis employing the 2-ΔΔCT method indicated a (6.89)-fold elevation in miR-3652 expression in tumors relative to controls. This suggests that miR-3652 may have an oncogenic role in carcinogenesis, potentially promoting BC development. In conclusion, our results demonstrated that elevated miR-3652 expression associates with the progression of BC, and this indicates that miR-3652 may possess an oncogenic function in tumorigenesis, possibly facilitating BC progression. Additional studies are required.